Novel antiangiogenic therapies in ovarian cancer. (July 2012) - Stuckey, Ashley; Dizon, Don S
Epithelial ovarian cancer is the leading cause of death in the developed world for women with gynecologic carcinomas. Despite the effectiveness of platinum salts and taxanes as primary treatments, approximately 80% of women will recur and for them prognosis with available treatments is poor. Of the novel mechanisms under active investigation, there is ample evidence to indicate that angiogenesis is important to the development, progression and poor prognosis of ovarian cancer. Novel treatments are therefore required. A number of agents are undergoing evaluation, including vascular disrupting agents, angiogenesis inhibitors, tyrosine kinase inhibitors and agents targeting the folate receptor. At present, Phase III data are only available for the VEGF-targeted monoclonal antibody, bevacizumab, and that has demonstrated a progression-free survival benefit when used in combination with first-line paclitaxel/carboplatin and continued as maintenance therapy. The strategy of inhibiting angiogenesis in ovarian cancer remains promising. However, other agents in development may point to other important targets in ovarian cancer.